2017
DOI: 10.1002/cbdv.201700073
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Characterization and Biological Activities of Phenolic‐Rich Fraction from Cauline Leaves of Isatis tinctoria L. (Brassicaceae) Growing in Sicily, Italy

Abstract: The present work focused on the evaluation of the antioxidant and cytotoxic activities of the phenolic-rich fraction (ItJ-EAF) obtained from cauline leaves collected in January from Isatis tinctoria L. (Brassicaceae) growing wild around Acireale (Sicily, Italy). The total phenolic, flavonoid, and condensed tannin contents of the fraction were determined spectrophotometrically, whereas the phenolic profile was assessed by HPLC-PDA/ESI-MS analysis. A total of 20 compounds were positively identified and twelve ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 42 publications
0
49
0
1
Order By: Relevance
“…The anti-proliferative properties of the phenolic-rich fraction obtained from I. tinctoria cauline leaf polar extract has been demonstrated, which caused 80% and 65% growth inhibition in CAL-62 and 8505C cells, respectively, after 48 h of exposure at the maximum tested dose (0.1 mg/mL). The activity of the phenolic-rich fraction against these cell lines was similar to that of Sunitinib used as a positive control, when tested at the dose of 10 µM for 72 h [46].…”
Section: Anti-tumor Activitymentioning
confidence: 62%
See 3 more Smart Citations
“…The anti-proliferative properties of the phenolic-rich fraction obtained from I. tinctoria cauline leaf polar extract has been demonstrated, which caused 80% and 65% growth inhibition in CAL-62 and 8505C cells, respectively, after 48 h of exposure at the maximum tested dose (0.1 mg/mL). The activity of the phenolic-rich fraction against these cell lines was similar to that of Sunitinib used as a positive control, when tested at the dose of 10 µM for 72 h [46].…”
Section: Anti-tumor Activitymentioning
confidence: 62%
“…The calculated coefficient of determination (R 2 ) indicated that flavonoids were the phenolic compounds mainly involved in the observed antioxidant properties. Another study carried out by the same authors on the phenolic-rich fraction obtained from I. tinctoria cauline leaf polar extract confirmed that phenolics were mainly responsible for the good radical scavenging properties [46]. In particular, the activity has been mainly related to the flavonols detected in the fraction, which have all the essential structural elements for potent radical scavenging activity.…”
Section: Antioxidant Activitymentioning
confidence: 85%
See 2 more Smart Citations
“…Since phenolics are the main component responsible for antioxidant activity [22][23][24], this fraction was spectrophotometrically determined using the Folin-Ciocalteu assay. Anthocyanins (a subclass of phenolics) were also determined.…”
Section: Total Antioxidant Power and Phenolics Contentmentioning
confidence: 99%